Leadership and business decision making - Pérez Salas, Francisco Paul; Puente Riofrío, Mariana Isabel; Andrade Namcela, William Fernando; Uquillas Granizo, Gilma Gabriela (mktDESCUBRE; Vol 1 No 22 (2023): Twenty-second Edition (July - December), 2023)
Leadership and business decision making is a currently relevant topic, in a business world characterized by uncertainty and fierce competition, in this context, the research aims to analyze the influence of leadership on business decision making in the case study company. A qualitative research approach was used, which allowed analyzing the study variables, in the data analysis non-parametric tests were applied to test the hypothesis, through Spearman's correlation coefficient, a moderate correlation was established between leadership and decision making, thus concluding that as leadership levels increase so does the ability to make effective decisions, i.e., the study variables are intertwined, by virtue of which leadership allows making informed decisions.